Lời khai mạc của Chủ tịch Quốc hội tại kỳ họp thứ 10, Quốc hội khóa IX - Chủ tịch Quốc hội; Chủ tịch Quốc hội (Văn phòng Quốc hội, 1996)
Toàn văn lời khai mạc của Chủ tịch Quốc hội tại kỳ họp thứ 10, Quốc hội khóa IX